Are native species of Ria de Aveiro under invasion? The relations between local activities and environmental perceptions on marine biological resources - Luís, Sílvia; Pinho, Mariana; Lopes, Marta L.; Oliveira, Bruna R. F.; Sousa, Ana I.; Lillebø, Ana I. (Frontiers in Marine Science, 2025)
IntroductionThis study showcases how the end-users of Ria de Aveiro coastal lagoon (Portugal), perceive the threat of invasive alien species (IAS), as well as biodiversity loss, and how it relates to their local activities, environmental identity and risk perception. Previous studies in the region and elsewhere have demonstrated that invasive species might have an impact at the habitats and at the species levels, both with potential negative socio-economic implications for end-users, i.e., for citizens who rely on the ecosystem for their livelihoods. However, this relation is still not well understood.MethodsData drew on face-to-face questionnaires run in situ at the lagoon intertidal flats. Supported by maps, participants were invited to identify the presence of the habitat Zostera noltei (also known as Zostera noltii), and the species Diopatra neapolitana, Hediste diversicolor and Arenicola spp., as well as Ruditapes decussatus, Venerupis corrugata and Ruditapes philippinarum, and inquired about the extraction, preference, and preferred areas. Of the 174 participants, 83% were male, and 68% were private citizens. Their main reason to be in situ at the time of the questionnaire relates to local traditional activities. This study is driven by three main research questions focusing on the perspective of the Ria de Aveiro local community that rely on the lagoon for their livelihoods: i) How is the threat of IAS to native species perceived? ii) How are the relations between local activities and IAS perceived? iii) What is the impact of environmental perceptions on marine biological resources?ResultsThe research questions that drove this study enabled us to conclude that the threat posed by IAS and biodiversity loss is moderate and individuals perceive that most of the species have decreased in the past and/or will decrease in the future. End-user’s evidence spatial-distinct preferences in the lagoon area for species-specific harvesting, including alien species, mainly related to market demand and financial gain.DiscussionThe impact of environmental perceptions on marine biological resources, indicate that the inter-relations between environmental identity and risk perception might have unexpected effects that need to be better understood.